Concept and Implementation of Fiqh Education in Schools: Perspective Analysis Maslahah Mursalah - Ahmad, Nurasiah; Nafsiyati, Hilma; Fitriani, Saparia; Nursyamsi, Nursyamsi; Yusuf, M. (International Journal of Multidisciplinary Research of Higher Education, 2026)
The integration of fiqh education into schools has increasingly been realized through the practice of qurban as experiential learning, where teachers, staff, and students participate to instill religious values and social responsibility. However, questions arise regarding the legal validity of qurban performed by students who have not reached maturity (baligh) and whose financial obligations are often borne by parents, potentially creating burdens for families with limited economic capacity. This study aims to analyze Islamic legal perspectives on school-based qurban programs through the lens of maslahah mursalah (public benefit). Using a qualitative library research approach and content analysis of normative Islamic legal sources, the findings indicate that such practices are valid and beneficial when they meet the established conditions of qurban and align with maqasid al-shari‘ah, offering educational value in sacrifice, empathy, and communal solidarity. Conversely, if conducted under compulsion, imposing undue burdens, or resulting in greater harm than benefit, these practices may be deemed impermissible (haram). The implications highlight the importance of designing qurban education in schools that balance pedagogical goals with legal and ethical considerations to ensure voluntary participation and genuine benefit.